Hepatitis B and C infections among lymphoma patients: a national study in the Republic of Moldova - Negara, Ivan; Buruiana, Sanda; Tomacinschii, Victor; Dudnic, Cristina (The Journal of Infection in Developing Countries, 2022)
Introduction: Hepatitis B virus (HBV) and hepatitis C virus (HCV) represent common infections that are presumably associated with various types of lymphoma and specific clinical features. However, conclusive data are lacking and results from different regional studies are conflicting. Hence, a national study was performed in order to investigate potential associations between hepatitis infections and lymphoma in the Republic of Moldova. Methodology: Data were collected from newly diagnosed adult lymphoma patients from January 2020 to January 2022. Patients who were not tested for HBsAg and anti-HCV and those with an undetermined lymphoma subtype diagnosis were excluded from the study. Subjects with and without viral hepatitis were then evaluated on the basis of clinical and pathological characteristics. Results: One hundred and twenty-nine lymphoma patients were included in the study; 15 (11.6%) patients were diagnosed with hepatitis B, 21 (16.3%) patients with hepatitis C, and 1 (0.78%) patient was positive for both. The majority of hepatitis patients were over 60 years old (62.2%), presented with stage III or IV (81%), had normal lactate dehydrogenase (58.3%) and 0 or 1 extranodal sites (78.4%). The most common lymphoma subtypes were diffuse large B-cell lymphoma (64.9%) and marginal zone lymphoma (8.1%). We did not find any statistically significant differences between infected and uninfected lymphoma patients in regards to clinical features, specific lymphoma subtypes, and presence and location of extranodal involvement. Conclusions: Presence of hepatitis B or C virus infections is not associated with specific clinical and pathological features in Moldovan lymphoma patients.